2018
DOI: 10.5194/esurf-2018-52
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potentials and pitfalls of permafrost active layer monitoring using the HVSR method: A case study in Svalbard

Abstract: Abstract. Time-lapse monitoring of the sub-surface using ambient seismic noise is a popular method in environmental seismology. We assess the reliability of the Horizontal-to-Vertical Spectral Ratio (HVSR) method for monitoring seasonal permafrost active layer variability in northwest Svalbard. We observe complex HVSR variability between 1 and 50 Hz in the record of a temporary seismic deployment covering frozen and thawn soil conditions between April and August 2016. While strong variations are due to changin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Lastly, arrays of multiple seismic stations could provide insights into the spatial variations of subsurface properties and alterations. Recent studies have demonstrated the opportunities and challenges for passive seismic monitoring of permafrost environments through horizontal‐to‐vertical spectral ratios (Abbott et al, ; Köhler & Weidle, ; Kula et al, ; Overduin et al, ). To date, using ambient noise for seismic interferometry has yet to be fully investigated for spatiotemporal monitoring of permafrost and active‐layer processes.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, arrays of multiple seismic stations could provide insights into the spatial variations of subsurface properties and alterations. Recent studies have demonstrated the opportunities and challenges for passive seismic monitoring of permafrost environments through horizontal‐to‐vertical spectral ratios (Abbott et al, ; Köhler & Weidle, ; Kula et al, ; Overduin et al, ). To date, using ambient noise for seismic interferometry has yet to be fully investigated for spatiotemporal monitoring of permafrost and active‐layer processes.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this sensitivity, seismic methods, including both active and passive, can be utilized to characterize and monitor subsurface permafrost systems; prior studies have leveraged coda wave interferometry techniques to track subtle daily, monthly, and seasonal changes in seismic velocity ( δv / v ) in such environments (James et al., 2017, 2021; Lindner et al., 2021; Steinmann et al., 2021). Horizontal‐to‐vertical spectral ratio (HVSR) methods, which connect time variations of the dominant (resonance) frequency with seasonal subsurface changes above and/or within permafrost, have also been explored (Köhler & Weidle, 2019; Kula et al., 2018). Compared with active seismic monitoring (Kasahara et al., 2010; Stemland et al., 2021), however, these ambient noise based (passive) seismic methods sometimes suffer from biased signal retrieval from non‐uniform noise source distribution (Harmon et al., 2010; Lin et al., 2008) and limited spatial resolution in the case of sparse networks often used in passive studies (Clarke et al., 2011; Ratdomopurbo & Poupinet, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the H/V analysis over time is still not carried out routinely and is performed only in a few and peculiar cases. For example, temporal variations of the H/V ratios have been investigated for monitoring the permafrost active layer seasonal variability (Köhler & Weidle, 2019; Kula et al., 2018) and for monitoring the rock masses stability (Colombero et al., 2018). Lotti et al.…”
Section: Introductionmentioning
confidence: 99%